Co-designed strategies for delivery of positive newborn bloodspot screening results to parents: the ReSPoND mixed-methods study - Jane Chudleigh; Pru Holder; Francesco Fusco; James R Bonham; Mandy Bryon; Louise Moody; Stephen Morris; Ellinor K Olander; Alan Simpson; Holly Chinnery; Fiona Ulph; Kevin W Southern (NIHR Journals Library, 2022)
Background: Newborn bloodspot screening identifies presymptomatic babies who are affected by genetic or congenital conditions. Each year, around 10,000 parents of babies born in England are given a positive newborn bloodspot screening result for one of nine conditions that are currently screened for. Despite national guidance, variation exists regarding the approaches used to communicate these results to families; poor communication practices can lead to various negative sequelae. Objectives: Identify and quantify approaches that are currently used to deliver positive newborn bloodspot screening results to parents (phase 1). Develop (phase 2), implement and evaluate (phase 3) co-designed interventions for improving the delivery of positive newborn bloodspot screening results. Quantify the resources required to deliver the co-designed interventions in selected case-study sites and compare these with costs associated with current practice (phase 3). Design: This was a mixed-methods study using four phases, with defined outputs underpinned by Family Systems Theory. Setting: All newborn bloodspot screening laboratories in England (n = 13). Participants: Laboratory staff and clinicians involved in processing or communicating positive newborn bloodspot screening results, and parents of infants who had received a positive or negative newborn bloodspot screening result. Interventions: Three co-designed interventions that were developed during phase 2 and implemented during phase 3 of the study. Main outcome measure: Acceptability of the co-designed interventions for the communication of positive newborn bloodspot screening results. Results: Staff were acutely aware of the significance of a positive newborn bloodspot screening result and the impact that this could have on families. Challenges existed when communicating results from laboratories to relevant clinicians, particularly in the case of congenital hypothyroidism. Clinicians who were involved in the communication of positive newborn bloodspot screening results were committed to making sure that the message, although distressing for parents, was communicated well. Despite this, variation in communication practices existed. This was influenced by many factors, including the available resources and lack of clear guidance. Although generally well received, implementation of the co-designed interventions in practice served to illuminate barriers to acceptability and feasibility. The interventions would not influence NHS expenditure and could be cost neutral when delivered by teleconsultations. Limitations: Participants with a pre-existing interest in this topic may have been more likely to self-select into the study. The researchers are experienced in this field, which may have biased data collection and analysis. COVID-19 hindered implementation and related data collection of the co-designed interventions. Conclusions: There was variation in the processes used to report positive newborn bloodspot screening results from newborn bloodspot screening laboratories to clinical teams and then to families. The various practices identified may reflect local needs, but more often reflected local resource. A more consistent 'best practice' approach is required, not just in the UK but perhaps globally. The co-designed interventions represent a starting point for achieving this. Future work: Future work should include a national evaluation study with predefined outcomes, accompanied by an economic evaluation, to assess the acceptability, feasibility and usability of the co-designed interventions in practice nationally. Trial registration: This trial is registered as ISRCTN15330120. Funding: This project was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme and will be published in full in Health and Social Care Delivery Research; Vol. 10, No. 19. See the NIHR Journals Library website for further project information.